2014
DOI: 10.1111/cccr.12069
|View full text |Cite
|
Sign up to set email alerts
|

Sports Television Reporters and the Negotiation of Fragmented Professional Identities

Abstract: This research examines the professional identities of sports television reporters at a regional sports network (RSN) in a major East Coast market. The ethnographic techniques of participant observation and interviews with these sports television news gatherers provide an in-depth look at the increasingly complex work facing sports journalists in this specific area of the sports-media complex. The study's findings reveal that women and African American sports television reporters working at this RSN said they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Instead, women are placed in a situation in which it appears to be a smarter career move not to promote other women (or events involving women), instead maintaining the status quo of the traditional male dominance in their profession in order to succeed themselves. This concept of fragmented identity can create a scenario in which female sports broadcasters must negotiate between their social identity as a female and their professional identity as a journalist (Genovese, 2015; Hardin, Genovese, & Yu, 2009; Hardin & Shain, 2006).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Instead, women are placed in a situation in which it appears to be a smarter career move not to promote other women (or events involving women), instead maintaining the status quo of the traditional male dominance in their profession in order to succeed themselves. This concept of fragmented identity can create a scenario in which female sports broadcasters must negotiate between their social identity as a female and their professional identity as a journalist (Genovese, 2015; Hardin, Genovese, & Yu, 2009; Hardin & Shain, 2006).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Former female athletes may be able to highlight their athletic status as a way to bypass questions about their credibility and find access to a field that has historically been exclusionary. Moreover, once they are in the field, the high value assigned to athletic experience may inoculate them to some degree from the overwhelming perceptions of inadequacy directed toward women in general highlighted in research by Cummins, Ortiz, and Rankine (2019), Genovese (2014), Hardin and Shain (2006), and many others.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a survey by Sheffer and Schultz (2007) showed that sports directors rated male sports broadcasters as more knowledgeable about sports compared with female sports broadcasters, while surveys and experiments with fans have consistently shown that women are evaluated through a gendered lens and rated lower on measures of credibility (e.g., Cummins, Ortiz, & Rankine, 2019; Mudrick, Burton, & Lin, 2017). Moreover, these assessments manifest themselves in a space where women are often understood as interlopers in male terrain, a process that reinforces and justifies women’s exclusion (e.g., Autonovic & Whiteside, 2018; Genovese, 2014; Hardin & Shain, 2006; Harrison, 2018). Taken together, women who enter sports media step into a hegemonic process that not only privileges men, but normalizes and justifies women’s lack of representation, advancement opportunities, and the persistent critiques of women’s skills and practices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations